Method for producing superabsorbent polymer

By forming microporous structures in superabsorbent polymers, the micronization process is used to solve the problem of fine particles, the absorption performance and absorption rate are improved, and an efficient preparation method is achieved.

CN119137194APending Publication Date: 2024-12-13LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037715.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-13
Filing Date
2023-12-15
Publication Date
2024-12-13

Smart Images

  • Figure CN119137194A_ABST
    Figure CN119137194A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method for preparing a superabsorbent polymer and a superabsorbent polymer. More specifically, the present invention relates to a method for preparing a superabsorbent polymer which exhibits excellent absorption performance and significantly reduces the generation of fine particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0176831 filed on December 16, 2022, Korean Patent Application No. 10-2022-0177310 filed on December 16, 2022, and Korean Patent Application No. 10-2023-0181009 filed on December 13, 2023, filed in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present disclosure relates to a method for preparing a super absorbent polymer, and more particularly, to a method for preparing a super absorbent polymer that exhibits excellent absorption performance and significantly reduces the generation of fine particles. Background Art

[0004] Super absorbent polymer (SAP) is a synthetic polymer material that can absorb 500 to 1000 times its own weight in water. Various manufacturers have named it with different names, such as SAM (super absorbent material) and AGM (absorbent gel material). Such super absorbent polymers began to be practically used in sanitary products, and now they are widely used in water-retaining soil products for gardening, water-stopping materials for civil engineering and construction, sheets for seedling cultivation, preservatives for food circulation fields, or materials for plasters, etc.

[0005] These superabsorbent polymers have been widely used in the field of sanitary materials such as diapers or sanitary napkins. In such sanitary materials, superabsorbent polymers are generally contained in a state dispersed in pulp. However, in recent years, efforts have been made to provide sanitary materials such as diapers with thinner thickness. As part of such efforts, the development of so-called pulp-free diapers and the like in which the pulp content is reduced or no pulp is used at all is being actively carried out.

[0006] In the case of the above-mentioned sanitary material in which the pulp content is reduced or no pulp is used, the superabsorbent polymer is contained in a relatively high ratio, so that the superabsorbent polymer particles are inevitably contained in the multilayer in the sanitary material. In order for the entire superabsorbent polymer particles contained in the multilayer to more effectively absorb a large amount of liquid such as urine, the superabsorbent polymer is basically required to show excellent absorption performance as well as a high absorption rate.

[0007] Meanwhile, such a super absorbent polymer is generally prepared by performing the steps of: a step of polymerizing a monomer to prepare a hydrogel polymer containing a large amount of water; and a step of drying the hydrogel polymer and then pulverizing it into polymer particles having a desired particle size. However, when the hydrogel polymer is dried and then pulverized as described above, a large amount of fine powder is generated, which leads to a problem of lowering the physical properties, particularly the absorption performance, of the finally prepared super absorbent polymer.

[0008] Therefore, in order to reuse the fine powder, the fine powder is generally mixed with water for agglomeration to produce a fine reassembly, which is then added to processes such as drying / crushing / classification, etc. However, the water used here may cause problems such as increased energy use during drying and increased load on equipment, which may reduce productivity in superabsorbent polymer production.

[0009] Meanwhile, the most common method for increasing the absorption rate is to enlarge the surface area of ​​the superabsorbent polymer by forming a porous structure in the superabsorbent polymer. In order to increase the surface area of ​​the superabsorbent polymer, a method of forming a porous structure in the base resin powder by including a foaming agent in the monomer composition and performing cross-linking polymerization is generally selected.

[0010] However, the use of a foaming agent has the disadvantage of reducing the physical properties of the superabsorbent polymer, such as surface tension, permeability or bulk density, and increasing the generation of fine particles. Therefore, there is a constant need to develop a technology that can increase the absorption rate of superabsorbent polymers without using a foaming agent.

[0011] Therefore, in order to fundamentally solve these problems, there is a constant demand for the development of a technology for preparing a super absorbent polymer without generating fine particles. Summary of the invention

[0012] [Technical issues]

[0013] Therefore, a method for preparing a superabsorbent polymer is provided, which forms micropores in the polymer through a micronization process to increase the surface area, thereby exhibiting excellent absorption performance, while significantly improving the absorption rate and significantly reducing the generation of fine particles during the process.

[0014] [Technical solution]

[0015] In order to solve the above problems, a method for preparing a superabsorbent polymer is provided, which comprises the following steps:

[0016] Polymerizing a monomer composition containing a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator to form a polymer in which the water-soluble ethylenically unsaturated monomer having an acidic group and the internal crosslinking agent are crosslinked and polymerized (step 1);

[0017] micronizing the polymer at a speed of 500 rpm to 4,000 rpm (step 2);

[0018] neutralizing at least some of the acidic groups of the polymer (step 3);

[0019] drying the micronized and neutralized polymer to obtain dry superabsorbent polymer particles (step 4); and

[0020] Super absorbent polymer particles are prepared by pulverizing the dried super absorbent polymer particles (step 5).

[0021] [Beneficial Effects]

[0022] According to the preparation method of the superabsorbent polymer disclosed in the present invention, a superabsorbent polymer can be provided, which forms micropores in the polymer through a micronization process to increase the surface area, thereby exhibiting excellent absorption performance, while significantly improving the absorption rate and significantly reducing the generation of fine particles during the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a flow chart of a method for preparing a super absorbent polymer according to one embodiment of the present disclosure.

[0024] Figure 2 is a SEM image of a polymer prepared by the method for preparing a super absorbent polymer according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0025] The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular form is intended to also include the plural form. It will be further understood that when used in this specification, the terms "comprising", "having" or "having" specify the presence of the features, steps, components or combinations thereof, but do not exclude the presence or addition of one or more other features, steps, components or combinations thereof.

[0026] Since the present invention can be modified in various ways and has various forms, its specific embodiments are shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific forms disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the concept and technical scope of the present invention.

[0027] Since the present invention can be modified in various ways and has various forms, its specific embodiments are shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific forms disclosed, and it should be understood that the present invention includes all modifications, equivalents and substitutions within the concept and technical scope of the present invention.

[0028] Hereinafter, a preparation method of a super absorbent polymer and a super absorbent polymer of the present disclosure will be described in more detail.

[0029] The terms used herein are intended to refer to specific embodiments only and are not intended to limit the present invention. In addition, as used herein, the singular form also includes the plural form, unless the phrase clearly indicates otherwise.

[0030] According to one embodiment of the present disclosure, there is provided a method for preparing a superabsorbent polymer, comprising the following steps:

[0031] Polymerizing a monomer composition containing a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator to form a polymer in which the water-soluble ethylenically unsaturated monomer having an acidic group and the internal crosslinking agent are crosslinked and polymerized (step 1);

[0032] micronizing the polymer at a speed of 500 rpm to 4,000 rpm (step 2);

[0033] neutralizing at least some of the acidic groups of the polymer (step 3);

[0034] drying the micronized and neutralized polymer to obtain dry superabsorbent polymer particles (step 4); and

[0035] Super absorbent polymer particles are prepared by pulverizing the dried super absorbent polymer particles (step 5).

[0036] The term "polymer" in the present disclosure is in a state where water-soluble ethylenically unsaturated monomers are polymerized, and may include all moisture content ranges or all particle size ranges.

[0037] In addition, the term "superabsorbent polymer" is used to cover all cross-linked polymers or base resins in the form of powder composed of superabsorbent polymer particles in which the cross-linked polymer is pulverized, and the cross-linked polymer or the base resin is further processed, such as drying, pulverizing, classifying, surface cross-linking, etc., to bring it into a state suitable for commercialization, as the case may be.

[0038] In addition, the term "fine powder" or "fine particles" refers to particles having a particle size of less than 150 μm among superabsorbent polymer particles. The particle size of these polymer particles can be measured according to EDANA (European Disposables and Nonwovens Association) WSP 220.3.

[0039] In addition, the term "mincing" refers to cutting the hydrogel polymer into small pieces on the millimeter scale to improve drying efficiency, and is used separately from pulverization to a micron or normal particle level.

[0040] In addition, the term "micronization" means pulverizing a hydrogel polymer to a particle size of several tens to several hundreds of micrometers, and is used separately from "mincing".

[0041] The hydrogel polymer obtained by polymerization of acrylic monomers is sold as a superabsorbent polymer in the form of powder through processes such as drying, pulverization, classification and surface cross-linking. Recently, attempts have been made to provide a superabsorbent polymer showing a more improved absorption rate.

[0042] The most common method to increase the absorption rate is to increase the surface area of ​​the superabsorbent polymer by forming a porous structure in the superabsorbent polymer. In order to increase the surface area of ​​the superabsorbent polymer, a method of forming a porous structure in the base resin powder by including a foaming agent in the monomer composition and then performing cross-linking polymerization is generally selected.

[0043] However, the use of a foaming agent has the disadvantage of reducing the physical properties of the superabsorbent polymer, such as surface tension, permeability or bulk density, and increasing the generation of fine particles. Therefore, there is a constant need to develop a technology that can increase the absorption rate of superabsorbent polymers without using a foaming agent.

[0044] Meanwhile, superabsorbent polymers are conventionally prepared by the following process: a water-soluble ethylenically unsaturated monomer having an acidic group that is at least partially neutralized is cross-linked and polymerized in the presence of an internal cross-linking agent and a polymerization initiator to form a hydrogel polymer, and then the formed hydrogel polymer is dried and subsequently crushed into a desired particle size. At this time, a shredding process of cutting the hydrogel polymer into particles of several millimeters is usually performed before the drying process to facilitate the drying of the hydrogel polymer and improve the efficiency of the pulverization process. However, due to the viscosity of the hydrogel polymer in this shredding process, the hydrogel polymer cannot be crushed into micro-sized particles, but becomes an agglomerated gel. When the hydrogel polymer in the form of an agglomerated gel is dried, a plate-like dried product is formed. In order to crush it into micro-sized particles, a multi-stage pulverization process is required, so there is a problem of generating many fine particles in the process.

[0045] Specifically, superabsorbent polymers are conventionally prepared by comprising the following steps:

[0046] (Neutralization) neutralizing at least some of the acidic groups of the water-soluble ethylenically unsaturated monomer;

[0047] (polymerization) forming a hydrogel polymer by cross-linking polymerization of a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups in the presence of an internal cross-linking agent and a polymerization initiator;

[0048] (Chopping) Chopping the hydrogel polymer;

[0049] (Drying) drying the chopped hydrogel polymer; and

[0050] (Pulverization / Classification) The dried polymer is pulverized and then classified into normal particles and fine particles.

[0051] As described above, the shredded hydrogel polymer has an agglomerated gel shape with a size of about 1 cm to 10 cm. This shredded hydrogel polymer is laminated on a belt made of a perforated plate at the bottom and dried by hot air supplied from the bottom or the top. Since the polymer dried by the above-mentioned drying method has a plate shape rather than a granular shape, the classification step after pulverization is carried out by coarse pulverization, then classification, then fine pulverization again, and then classification, so that the particles to be prepared become normal particles, that is, particles with a particle size of 150 μm to 850 μm. Since the amount of fine particles separated in the final classification step is about 20% to about 30% by weight based on the total weight of the final superabsorbent polymer, the separated fine particles are mixed with an appropriate amount of water, reorganized, and then introduced in the shredding step or before drying for reuse.

[0052] However, when the fine powder reconstituted with water is reinjected into a pulverizing or drying process to reuse the fine particles, problems such as increased equipment load and / or energy consumption occur, and the remaining fine particles that have not been classified cause deterioration in physical properties of the superabsorbent polymer.

[0053] Therefore, the present inventors have found that the generation of fine particles in the conventional preparation method is largely affected by the pulverization process, and that the generation of fine particles in the preparation process can be significantly reduced by controlling the pulverization conditions of the polymer.

[0054] Meanwhile, the most common method for improving the absorption rate is to increase the surface area of ​​the superabsorbent polymer by forming a porous structure in the superabsorbent polymer. In order to increase the surface area of ​​the superabsorbent polymer, a method of forming a porous structure in a base resin powder by including a foaming agent in a monomer composition and then performing cross-linking polymerization is generally selected.

[0055] However, the use of a foaming agent has the disadvantages of reducing the physical properties of the superabsorbent polymer, such as surface tension, permeability or bulk density, and increasing the generation of fine particles due to the pores formed by the foaming agent making the shape of the particle surface sharp. Therefore, there is a constant need to develop a technology that can increase the absorption rate of superabsorbent polymers without using a foaming agent.

[0056] As a result of repeated studies to solve this problem, it was confirmed that when polymerization is first performed to form a polymer in a state where the acidic group is not neutralized, the hydrogel polymer is micronized by applying a high-intensity mechanical shear force, and then the acidic group of the polymer is neutralized; when the acidic group of the polymer is neutralized to form a hydrogel polymer, and then the hydrogel polymer is micronized; or when the acidic group present in the polymer is neutralized while micronizing, agglomerated hydrogel particles with micropores can be formed. Since the hydrogel polymer prepared by this process is manufactured in the form of particles with stable micropores of less than 100 μm, and the pulverization and drying processes are carried out under milder conditions, the generation of fine particles in the process can be significantly reduced. In addition, it was confirmed that the micronization process using a high-intensity mechanical shear force can significantly increase the absorption rate by forming micropores in the hydrogel polymer without using a separate foaming agent in the polymerization step.

[0057] Meanwhile, the micronization process of the hydrogel polymer may be preferably performed in the presence of a surfactant. When a surfactant is used in the micronization step, agglomeration of particles can be effectively controlled, and thus productivity can be further improved by reducing the load of the machine.

[0058] In addition, when polymerization is first performed in an unneutralized state to form a polymer and then the acidic groups present in the polymer are neutralized, a longer chain polymer can be formed, and thus the content of extractable components present in a non-crosslinked state due to incomplete crosslinking can be reduced.

[0059] The extractable components have the property of being easily dissolved when the superabsorbent polymer comes into contact with a liquid. When the content of the extractable components is high, most of the dissolved extractable components remain on the surface of the superabsorbent polymer and make the superabsorbent polymer sticky, thereby reducing permeability. Therefore, it is important to keep the content of the extractable components low in terms of permeability.

[0060] According to one embodiment of the present disclosure, since the polymerization is performed in an unneutralized state, the content of extractable components is reduced, and thus the permeability of the super absorbent polymer may be improved.

[0061] In addition, the super absorbent polymer prepared according to one embodiment of the present disclosure may have a uniform particle size distribution, and thus may provide a super absorbent polymer excellent in absorption properties such as centrifugal retention capacity and pressurized absorbency, rewetting characteristics, and absorption rate.

[0062] Hereinafter, a method for preparing a super absorbent polymer according to one embodiment will be described in more detail for each step.

[0063] Preparation of superabsorbent polymers

[0064] Step 1: Aggregation step

[0065] First, a monomer composition containing a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator is polymerized to form a polymer in which the water-soluble ethylenically unsaturated monomer having an acidic group is crosslinked and polymerized with the internal crosslinking agent.

[0066] The above steps may include the steps of preparing a monomer composition by mixing a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator, and polymerizing the monomer composition to form a polymer.

[0067] The water-soluble ethylenically unsaturated monomer may be any monomer commonly used to prepare superabsorbent polymers. Specifically, the water-soluble ethylenically unsaturated monomer may be a compound represented by the following Chemical Formula 1:

[0068] [Chemical formula 1]

[0069] R-COOM'

[0070] In Chemical Formula 1,

[0071] R is a C2 to C5 alkyl group having an unsaturated bond, and

[0072] M' is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0073] Preferably, the monomer may be at least one selected from the group consisting of (meth)acrylic acid and monovalent (alkali) metal salts, divalent metal salts, ammonium salts and organic amine salts of the acid.

[0074] When (meth) acrylic acid and / or its salt is used as a water-soluble ethylenically unsaturated monomer, it is advantageous to obtain a superabsorbent polymer having improved absorption properties. In addition, as monomers, maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylate, (meth)acrylate 2-hydroxyethyl, (meth)acrylate 2-hydroxypropyl, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate and (N,N)-dimethylaminopropyl (meth)acrylamide, etc. can be used.

[0075] Here, the water-soluble ethylenically unsaturated monomer has an acidic group. As mentioned above, conventionally, the polymer is formed by cross-linking polymerization of monomers in which at least some of the acidic groups are neutralized by a neutralizing agent. Specifically, in the step of mixing the water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, a polymerization initiator and a neutralizing agent, at least some of the acidic groups of the water-soluble ethylenically unsaturated monomer are neutralized.

[0076] However, according to one embodiment of the present disclosure, polymerization is first performed in a state where the acidic group of the water-soluble ethylenically unsaturated monomer is not neutralized to form a polymer.

[0077] A water-soluble ethylenically unsaturated monomer (e.g., acrylic acid) whose acidic group is not neutralized is in a liquid state at room temperature and has high miscibility with the solvent (water), and therefore exists in the monomer composition as a mixed solution. On the other hand, a water-soluble ethylenically unsaturated monomer whose acidic group is neutralized is in a solid state at room temperature and has different solubility depending on the temperature of the solvent (water), and has a lower solubility at a lower temperature.

[0078] Compared with the monomer whose acidic group is neutralized, the water-soluble ethylenically unsaturated monomer whose acidic group is not neutralized has higher solubility or miscibility with the solvent (water), and thus does not precipitate even at low temperatures, thus facilitating long-term polymerization at low temperatures. Therefore, by using the water-soluble ethylenically unsaturated monomer whose acidic group is not neutralized for long-term polymerization, a polymer having a higher molecular weight and a uniform molecular weight distribution can be stably formed.

[0079] In addition, a long-chain polymer can be formed, thereby achieving an effect of reducing the content of extractable components that exist in a non-crosslinked state due to incomplete polymerization or crosslinking.

[0080] In addition, when polymerization is first carried out to form a polymer in a state where the acidic groups of the monomers are not neutralized, and then micronized in the presence of a surfactant after neutralization; neutralization is carried out after micronization in the presence of a surfactant; or when the acidic groups present in the polymer are neutralized while micronized, a large amount of surfactant may be present on the surface of the polymer to fully play the role of reducing the adhesion of the polymer.

[0081] The concentration of the water-soluble ethylenically unsaturated monomer in the monomer composition may be about 20 to 60 wt %, or about 20 to 40 wt %, taking into account polymerization time and reaction conditions.

[0082] The term "internal crosslinking agent" as used herein is a term used to distinguish it from a surface crosslinking agent generally used to crosslink the surface of superabsorbent polymer particles, and is used to form a polymer having a crosslinked structure by introducing crosslinks between unsaturated bonds of the above-mentioned water-soluble ethylenically unsaturated monomers.

[0083] The crosslinking in the above steps is performed both on the surface and inside, but when the surface crosslinking process of the super absorbent polymer particles is performed, the surface of the super absorbent polymer particles finally prepared can have a structure newly crosslinked by the surface crosslinking agent, and the interior of the particles can maintain a structure crosslinked by the internal crosslinking agent.

[0084] According to one embodiment of the present disclosure, the internal cross-linking agent may include any one or more of a multifunctional acrylate compound, a multifunctional allyl compound, or a multifunctional vinyl compound.

[0085] Non-limiting examples of multifunctional acrylate compounds may include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,2-butylene glycol di(meth)acrylate, di(meth)acrylate), hexanediol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol di(meth)acrylate and glycerol tri(meth)acrylate, and these may be used alone or in combination of two or more.

[0086] Non-limiting examples of the multifunctional allyl compounds may include ethylene glycol diallyl ether, diethylene glycol diallyl ether, triethylene glycol diallyl ether, tetraethylene glycol diallyl ether, polyethylene glycol diallyl ether, propylene glycol diallyl ether, tripropylene glycol diallyl ether, polypropylene glycol diallyl ether, 1,4-butanediol diallyl ether, 1,2-butylene glycol diallyl ether, ether), hexanediol diallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, dipentaerythritol diallyl ether, dipentaerythritol triallyl ether, dipentaerythritol tetraallyl ether, dipentaerythritol pentaallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, glycerol diallyl ether and glycerol triallyl ether, and these can be used alone or in combination of two or more.

[0087] The limiting examples of multifunctional vinyl compounds can include ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, tripropylene glycol divinyl ether, polypropylene glycol divinyl ether, 1,4-butylene glycol divinyl ether (butanedioldivinyl ether), 1,2-butylene glycol divinyl ether (butylene glycoldivinyl ether), hexanediol divinyl ether, pentaerythritol divinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol divinyl ether, dipentaerythritol trivinyl ether, dipentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, trimethylolpropane divinyl ether, trimethylolpropane trivinyl ether, glycerol divinyl ether and glycerol trivinyl ether etc., and these can be used alone or in combination of two or more. Preferably, pentaerythritol triallyl ether can be used.

[0088] In the above-mentioned multifunctional allyl compound or multifunctional vinyl compound, two or more unsaturated groups contained in the molecule are combined with the unsaturated bond of the water-soluble ethylenically unsaturated monomer or the unsaturated bond of another internal crosslinking agent, thereby forming a crosslinked structure during the polymerization process. In addition, unlike the acrylate compound containing an ester bond (-(C=O)O-) in the molecule, the crosslinking can be maintained more stably even in the neutralization process after the above-mentioned polymerization reaction.

[0089] Therefore, the gel strength of the final super absorbent polymer can be improved, the process stability can be improved during the discharge process after polymerization, and the amount of extractable components can be minimized.

[0090] The cross-linking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of the internal cross-linking agent can be carried out in the presence of a polymerization initiator and, if necessary, a thickener, a plasticizer, a storage stabilizer, an antioxidant, and the like.

[0091] In the monomer composition, based on 100 parts by weight of water-soluble ethylenically unsaturated monomers, the usage amount of the internal crosslinking agent can be 0.01 to 5 parts by weight. For example, the usage amount of the internal crosslinking agent can be more than 0.01 parts by weight, more than 0.05 parts by weight or more than 0.1 parts by weight, and less than 5 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight or less than 0.7 parts by weight. When the content of the internal crosslinking agent is too low, crosslinking cannot fully occur, making it difficult to achieve a strength higher than an appropriate level. When the content of the internal crosslinking agent is too high, the internal crosslinking density increases, making it difficult to achieve the required centrifugal retention capacity.

[0092] The polymer formed using such an internal crosslinking agent has a three-dimensional network structure in which a main chain formed by polymerization of a water-soluble ethylenically unsaturated monomer is crosslinked by the internal crosslinking agent. When the polymer has a three-dimensional network structure in this manner, the centrifugal retention capacity and pressure absorption rate of various physical properties as a superabsorbent polymer can be significantly improved compared to a polymer having a two-dimensional linear structure that is not additionally crosslinked by the internal crosslinking agent.

[0093] According to one embodiment of the present disclosure, the step of forming a polymer by polymerizing the monomer composition may be performed in a batch reactor for more than 1 hour.

[0094] In the conventional preparation method of superabsorbent polymer composition, polymerization method is roughly divided into thermal polymerization and photopolymerization according to the energy source of polymerization. In the case of thermal polymerization, it is usually carried out in a reactor (such as a kneader) equipped with a stirring shaft. In the case of photopolymerization, it can be carried out in a container with a flat bottom.

[0095] Meanwhile, when the polymerization is carried out in a continuous manner, for example, in a reactor equipped with a conveyor belt and a stirring shaft, a new monomer composition is supplied to the reactor while the polymerized product moves. Therefore, polymers having different polymerization degrees are mixed, and thus, it is difficult to achieve uniform polymerization throughout the monomer composition, and overall physical properties may be deteriorated.

[0096] However, according to one embodiment of the present disclosure, since polymerization is performed in a fixed bed type in a batch reactor, there is little risk of polymers having different degrees of polymerization being mixed, and thus a polymer having uniform quality can be obtained.

[0097] In addition, the polymerization step is carried out in a batch reactor with a predetermined volume, and compared with being polymerized in a continuous manner in a reactor equipped with a conveyor belt, the time that polyreaction is carried out is longer, for example more than 1 hour, more than 3 hours or more than 6 hours. Preferably, 1 hour to 24 hours, 1 hour to 18 hours, 1 hour to 12 hours or 1 hour to 8 hours can be carried out. Although the polymerization time is long as mentioned above, because polymerization is carried out on unneutralized water-soluble ethylenically unsaturated monomers, monomer is difficult for separating out. Therefore, be conducive to carrying out long-time polymerization.

[0098] Meanwhile, since the polymerization in the batch reactor of the present disclosure uses a thermal polymerization method, a thermal polymerization initiator is used as a polymerization initiator.

[0099] In addition, one or more initiators selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide and ascorbic acid can be used as thermal polymerization initiators. Specifically, sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8) and ammonium persulfate ((NH4)2S2O8) can be used as examples of persulfate initiators; and 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutyronitrile (2-(carbamoylazo)isobutylonitril), 2,2-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride and 4,4-azobis-(4-cyanovaleric acid) can be used as examples of azo initiators. More various thermal polymerization initiators are well disclosed in “Principle of Polymerization (Wiley, 1981)” by Odian, page 203, and the present disclosure is not limited thereto.

[0100] Based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer, the amount of the polymerization initiator used may be 2 parts by weight or less. When the concentration of the polymerization initiator is too low, the polymerization rate may slow down, and a large amount of residual monomers may be extracted from the final product. On the contrary, when the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network become shorter, so that the extractable content increases and the pressure absorption rate decreases, thereby reducing the physical properties of the polymer.

[0101] Meanwhile, in one embodiment of the present disclosure, polymerization may be initiated by adding a reducing agent capable of forming a redox pair with the initiator.

[0102] Specifically, when an initiator and a reducing agent are added to a polymer solution, they react with each other to form free radicals.

[0103] Since the formed free radicals react with the monomers and the reactivity of the redox reaction between the initiator and the reducing agent is high, polymerization is initiated even when only a small amount of initiator and reducing agent are added, so there is no need to increase the process temperature. Therefore, low-temperature polymerization is possible and changes in the physical properties of the polymer solution can be minimized.

[0104] The polymerization reaction using the redox reaction can smoothly occur even at a temperature around room temperature (25° C.) or lower. For example, the polymerization reaction can be performed at a temperature of 5° C. to 25° C. or 5° C. to 20° C.

[0105] In one embodiment of the present disclosure, when a persulfate initiator is used as an initiator, the reducing agent may be at least one selected from the group consisting of sodium pyrosulfite (Na2S2O5), tetramethylethylenediamine (TMEDA), a mixture of iron (II) sulfate and EDTA (FeSO4 / EDTA), sodium formaldehyde sulfoxylate and disodium 2-hydroxy-2-sulfinacetic acid.

[0106] In one example, potassium persulfate is used as an initiator and disodium 2-hydroxy-2-sulfinatoacetate is used as a reducing agent; ammonium persulfate is used as an initiator and tetramethylethylenediamine is used as a reducing agent; or sodium persulfate is used as an initiator and sodium formaldehyde sulfoxylate is used as a reducing agent.

[0107] In another embodiment of the present disclosure, when a hydrogen peroxide-based oxidant is used as an initiator, the reducing agent may be at least one selected from the group consisting of ascorbic acid, sucrose, sodium sulfite (Na2SO3), sodium metabisulfite (Na2S2O5), tetramethylethylenediamine (TMEDA), a mixture of iron (II) sulfate and EDTA (FeSO4 / EDTA), sodium formaldehyde sulfoxylate, disodium 2-hydroxy-2-sulfinyl acetate and disodium 2-hydroxy-2-sulfoacetate.

[0108] If necessary, the monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant.

[0109] In addition, the monomer composition containing the monomer can be, for example, a solution form dissolved in a solvent such as water, and the solid content in the monomer composition in the solution form, i.e., the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator can be appropriately adjusted in consideration of the polymerization time and the reaction conditions. For example, the solid content in the monomer composition can be 10 to 80% by weight, 15 to 60% by weight, or 30 to 50% by weight.

[0110] At this time, any solvent capable of dissolving the above components can be used without limitation. For example, the solvent can be selected from at least one of water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butylene glycol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate and N,N-dimethylacetamide.

[0111] Since the polymer obtained in this manner is polymerized using an unneutralized ethylenically unsaturated monomer, a polymer having a high molecular weight and a uniform molecular weight distribution can be formed, and the content of extractable components can be reduced.

[0112] In addition, the water content of the polymer may be 30 to 80% by weight. For example, the water content of the polymer may be 30% by weight or more, 45% by weight or more, or 50% by weight or more, and 80% by weight or less, 70% by weight or less, or 60% by weight or less.

[0113] When the water content of the polymer is too low, it may not be effectively pulverized because it is difficult to ensure an appropriate surface area in the subsequent pulverization step. When the water content of the polymer is too high, it may be difficult to pulverize the polymer to a desired particle size due to increased pressure applied in the subsequent pulverization step.

[0114] At this time, the "water content" in the present disclosure is the content of water in the total weight of the polymer, which means a value obtained by subtracting the weight of the dry polymer from the weight of the polymer. Specifically, the water content is defined as a value calculated by measuring the weight loss due to evaporation of water from the polymer in the process of increasing the temperature of the polymer in a crushed state by infrared heating and drying it. At this time, the drying conditions for measuring the water content are as follows: the temperature is increased to about 180°C and maintained at 180°C, and the total drying time is 40 minutes, including a 5-minute heating step.

[0115] Step 2: Micronization step

[0116] Next, a step of micronizing the polymer at a rotation speed of 500 rpm to 4,000 rpm is performed. This is a step in which the polymer is not chopped into millimeter size, but is cut into tens to hundreds of micron sizes and agglomerated at the same time. In this step, a high-intensity mechanical shear force is applied, so pores of 100 μm or less are easily formed in the polymer, which increases the surface roughness and significantly increases the total surface area of ​​the polymer due to the pores formed inside and outside the polymer particles. Since the pores are formed in a more stable form than the pores formed using a foaming agent in the polymerization step, the fine particles generated by the pores in the subsequent process can be significantly reduced. The surface area of ​​the superabsorbent polymer particles prepared by this step is greatly increased, and the absorption rate can be significantly improved.

[0117] Figure 2 An SEM image of a final super absorbent polymer prepared after the micronization process of step 2 in the method for preparing a final super absorbent polymer according to one embodiment of the present disclosure is shown, and it is confirmed that fine pores are uniformly formed inside and outside the polymer.

[0118] The micronization process is carried out at a rotation speed of 500rpm to 4,000rpm. When the rotation speed of the process is less than 500rpm, it is difficult to form the required sufficient pores, and therefore it is difficult to expect the rapid absorption rate and productivity required by the present disclosure. In addition, when the rotation speed exceeds 4,000rpm, the polymer chain may be damaged by excessive shear force, and as a result, the extractable content may increase and the overall physical properties of the prepared superabsorbent polymer may deteriorate. Preferably, the micronization process can be carried out at 1,500rpm to 3,500rpm, or 2,000rpm to 3,000rpm. Within this range, it is easy to form the required micropores without the above problems.

[0119] According to one embodiment of the present disclosure, the micronization step is performed by applying a high-intensity mechanical shear force, and thus, the step is performed by a high shear pulverizer.

[0120] The high shear pulverizer may include: a main body including a transmission space in which a polymer is transmitted; a screw component rotatably mounted inside the transmission space to move the polymer; a drive motor providing a rotational driving force to the screw component; a cutter component mounted in the main body to pulverize the polymer; and a perforated plate having a plurality of holes and capable of discharging the polymer pulverized by the cutter component to the outside of the main body.

[0121] At this time, the rotation speed of the driving motor of the high shear pulverizer is the same as that in step 4 above.

[0122] Furthermore, the hole size provided in the perforated plate of the high shear pulverizer may be 1 mm to 25 mm, 5 mm to 20 mm, or 5 mm to 15 mm.

[0123] When a polymer is micronized using a high shear pulverizer, a smaller particle size distribution can be achieved, and then the drying and pulverization process can be carried out under milder conditions, thereby preventing the generation of fine particles. At the same time, appropriate micropores are formed on the polymer surface, increasing the surface area, thereby significantly improving the absorption rate.

[0124] According to one embodiment of the present disclosure, micronization can be performed more than once, preferably 1 to 6 times, 1 to 4 times, or 1 to 3 times. It can be performed using multiple pulverizers or using a single pulverizer including multiple perforated plates and / or multiple cutter components. Alternatively, some of the multiple pulverizers may include multiple perforated plates and / or multiple cutter components.

[0125] According to one embodiment of the present disclosure, a surfactant may be additionally used in the micronization step, so that agglomeration of polymer particles may be effectively controlled. Therefore, productivity may be further improved by reducing the load of a machine used in pulverization.

[0126] Preferably, the surfactant may be a compound represented by the following Chemical Formula 2 or a salt thereof, but the present disclosure is not limited thereto:

[0127] [Chemical formula 2]

[0128]

[0129] In chemical formula 2,

[0130] A1, A2 and A3 are each independently a single bond, a carbonyl group, Provided that at least one of these is a carbonyl group or wherein m1, m2 and m3 are each independently an integer from 1 to 8, each connected to the adjacent oxygen atom, and Connect to adjacent R1, R2 and R3 respectively.

[0131] R1, R2 and R3 are each independently hydrogen, C6 to C18 straight chain or branched chain alkyl or C6 to C18 straight chain or branched chain alkenyl, and

[0132] n is an integer of 1-9.

[0133] The surfactant is mixed with the polymer and added so that the micronization step can be easily performed without agglomeration.

[0134] The surfactant represented by Chemical Formula 2 is a nonionic surfactant and has excellent surface adsorption properties through hydrogen bonding even with unneutralized polymers, and is therefore suitable for achieving the desired agglomeration control effect. On the other hand, anionic surfactants other than nonionic surfactants, when mixed with a polymer neutralized with a neutralizing agent such as NaOH or Na2SO4, react with the polymer through the Na ionization at the carboxyl substituent of the polymer. + When mixed with unneutralized polymers, the adsorption efficiency of the polymer is relatively reduced due to competition with the anions of the carboxyl substituents of the polymer.

[0135] Specifically, in the surfactant represented by Chemical Formula 2, the hydrophobic functional groups are the terminal functional groups R1, R2 and R3 (if not hydrogen), and the hydrophilic functional groups include the glycerol-derived portion in the chain and the terminal hydroxyl group (when A n is a single bond and R n When n is hydrogen, n=1 to 3). Here, the glycerol-derived portion and the terminal hydroxyl group are hydrophilic functional groups and play a role in improving the adsorption performance to the polymer surface. Therefore, the aggregation of the superabsorbent polymer particles can be effectively suppressed.

[0136] In Chemical Formula 2, R1, R2 and R3 (if not hydrogen) of the hydrophobic functional group are each independently C6 to C18 straight or branched alkyl or C6 to C18 straight or branched alkenyl. At this time, when R1, R2 and R3 (if not hydrogen) are alkyl or alkenyl groups with less than 6 carbon atoms, there is a problem that the chain length is too short to effectively control the agglomeration of the crushed particles. When R1, R2 and R3 (if not hydrogen) are alkyl or alkenyl groups with more than 18 carbon atoms, there may be a problem that the mobility of the surfactant is reduced and it may not be effectively mixed with the polymer, and the unit price of the composition increases due to the increase in the cost of the surfactant.

[0137] Preferably, R1, R2 and R3 are hydrogen, C6 to C18 straight chain or branched alkyl, such as 2-methylhexyl, n-heptyl, 2-methylheptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, or n-octadecyl, or C6 to C18 straight chain or branched alkenyl, such as 2-hexenyl, 2-heptenyl, 2-octenyl, 2-nonenyl, n-decenyl, 2-undecenyl, 2-dodecenyl, 2-tridecenyl, 2-tetradecenyl, 2-pentadecenyl, 2-hexadecenyl, 2-heptadecenyl, or 2-octadecenyl.

[0138] The surfactant may be selected from the compounds represented by the following Chemical Formulas 2-1 to 2-14:

[0139] [Chemical formula 2-1]

[0140]

[0141] [Chemical formula 2-2]

[0142]

[0143] [Chemical formula 2-3]

[0144]

[0145] [Chemical formula 2-4]

[0146]

[0147] [Chemical formula 2-5]

[0148]

[0149] [Chemical formula 2-6]

[0150]

[0151] [Chemical formula 2-7]

[0152]

[0153] [Chemical formula 2-8]

[0154]

[0155] [Chemical formula 2-9]

[0156]

[0157] [Chemical formula 2-10]

[0158]

[0159] [Chemical formula 2-11]

[0160]

[0161] [Chemical formula 2-12]

[0162]

[0163] [Chemical formula 2-13]

[0164]

[0165] [Chemical formula 2-14]

[0166]

[0167] Meanwhile, the amount of the surfactant used is not particularly limited, but may be about 3 parts by weight or less, preferably 2 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.1 parts by weight or less, 0.01 parts by weight or less, or 0.001 parts by weight or less, and 0.0001 parts by weight or more, based on 100 parts by weight of the polymer, depending on productivity or equipment load. When too much surfactant is used, the surface tension is reduced, and thus the overall physical properties of the final superabsorbent polymer may be deteriorated.

[0168] The method of mixing the surfactant with the polymer is not particularly limited and can be appropriately selected as long as it is a method capable of uniformly mixing the additive with the polymer. Specifically, the surfactant may be dry-mixed, dissolved in a solvent and then mixed in a solution state, or melted and then mixed.

[0169] For example, the surfactant can be mixed in the form of a solution dissolved in a solvent. At this time, all types of solvents including inorganic solvents and organic solvents can be used without limitation, but water is most appropriate in view of the ease of the drying process and the cost of the solvent recovery system. In addition, a method in which a surfactant in the form of a solution and a polymer are added to a reaction tank for mixing, a method in which a solution is sprayed after adding a polymer to a mixer, or a method in which a polymer and a solution are continuously supplied to a continuously operated mixer for mixing, etc. can be used.

[0170] Step 3: Neutralization Step

[0171] According to one embodiment of the present disclosure, a step of neutralizing at least some of the acidic groups of the polymer is performed (step 3), and the micronization step of step 2 and the neutralization step of step 3 can be performed sequentially, alternately or simultaneously.

[0172] In other words, a neutralizing agent may be added to the polymer to first neutralize the acidic groups, and then a surfactant may be added to the neutralized polymer to micronize the polymer mixed with the surfactant (performed in the order of step 3->step 2). Alternatively, the polymer may be neutralized and micronized by adding a neutralizing agent and a surfactant to the polymer simultaneously (performed in steps 2 and 3 simultaneously). Alternatively, the surfactant may be added first, and then the neutralizing agent may be added (performed in the order of step 2->step 3). Alternatively, the neutralizing agent and the surfactant may be added alternately. Alternatively, a surfactant may be added first for micronization, and then a neutralizing agent may be added to neutralize the product, and then additional surfactant may be added to the neutralized hydrogel polymer to further perform the micronization process.

[0173] Here, when the neutralization step is performed independently of the micronization step of step 2, it can be performed by pulverizing the polymer while adding the additive. More specifically, a screw extruder including a perforated plate having a plurality of holes can be used. The screw extruder is a device that performs pulverization under milder conditions than the high shear pulverizer used in the above-mentioned micronization step. The rotation speed may be about 50 rpm to 500 rpm, and the holes of the perforated plate may be about 3 mm to 25 mm, but are not limited thereto.

[0174] Here, as the neutralizing agent, a basic material capable of neutralizing an acidic group such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide may be used.

[0175] In addition, the degree of neutralization (referring to the degree of neutralization of the acidic groups included in the polymer by the neutralizer) can be preferably 50 to 90 % by mole, 60 to 85 % by mole, 65 to 85 % by mole or 65 to 75 % by mole. The scope of the degree of neutralization can change according to final physical properties. When the neutralization degree is too high, the absorbency of superabsorbent polymer may reduce, and the carboxyl concentration on the particle surface is too low, making it difficult to suitably carry out surface crosslinking in the subsequent process, causing pressurized absorbency or liquid permeability to reduce. On the contrary, too low a degree of neutralization not only deteriorates the absorbency of polymer, but also gives polymer the difficult-to-handle character, for example the character of elastic rubber.

[0176] Also, in order to uniformly neutralize the entire polymer, it may be desirable to allow a certain amount of time between the addition of the neutralizing agent and the micronization process.

[0177] Step 4: Drying Step

[0178] Next, a step of drying the micronized and neutralized polymer to prepare dried superabsorbent polymer particles is performed (step 4).

[0179] This step is a step of drying the moisture in super absorbent polymer particles obtained by neutralizing at least some of the acid groups of the polymer and micronizing the polymer.

[0180] In a typical manufacturing method of a super absorbent polymer, the drying step is performed so that the moisture content of the super absorbent polymer is about 1 to 20 wt %, about 4 to about 15 wt %, or about 6 to about 13 wt %. However, the present disclosure is not limited thereto.

[0181] Step 4 can be performed by fixed bed drying, mobile drying or a combination thereof.

[0182] According to one embodiment of the present disclosure, step 4 may be performed by a fixed bed drying method.

[0183] Fixed bed drying is a method in which the material to be dried is fixed on a porous iron plate or other floor through which air can pass, and hot air is passed from bottom to top through the material to dry it.

[0184] Since fixed bed drying dries in a plate shape without particle flow, it is difficult to simply perform uniform drying with hot air flow. Therefore, fixed bed drying requires fine control of hot air and temperature to obtain a uniform dried product with a high moisture content. In the present disclosure, bending of the plate-shaped dried product during drying is prevented by a method of switching the hot air from the bottom to the top, thereby preventing leakage of the hot air. In addition, the drying temperature of each section is changed so that the top layer, bottom layer, left layer and right layer, as well as the upper layer, middle layer and lower layer inside the dried product can be uniformly dried, with a moisture content deviation of less than 5%.

[0185] As equipment capable of drying by such a fixed bed drying method, a belt dryer or the like can be used, but the invention is not limited thereto.

[0186] Fixed bed drying can be performed at a temperature of about 80° C. to 200° C., preferably 90° C. to 200° C., 100° C. to 200° C., or 100° C. to 180° C. When the temperature is too low, for example, less than 80° C., the drying time may become too long. When the drying temperature is too high, for example, more than 200° C., a superabsorbent polymer having a moisture content lower than a desired moisture content may be obtained. Meanwhile, the drying temperature may refer to the temperature of the hot air used, or the temperature inside the equipment during the drying process.

[0187] According to one embodiment of the present disclosure, step 4 may be performed by mobile drying.

[0188] Mobile drying refers to a method of drying while mechanically agitating the material to be dried. In this case, the direction in which the hot air passes through the material can be the same as or different from the direction in which the material circulates. Alternatively, the material can be circulated inside the dryer and dried by passing a heat transfer fluid through a separate pipe outside the dryer.

[0189] As equipment capable of drying by such a mobile drying method, a horizontal mixer, a rotary kiln, a paddle dryer, a steam tube dryer or a commonly used mobile dryer can be used.

[0190] Mobile drying may be performed at a temperature of about 100° C. to 300° C., preferably 120° C. to 280° C., or 150° C. to 250° C. When the temperature is too low, for example, less than 100° C., the drying time may become too long. When the drying temperature is too high, for example, exceeding 300° C., the polymer chain of the superabsorbent polymer may be damaged, resulting in deterioration of physical properties, and a superabsorbent polymer having a moisture content lower than a desired moisture content may be obtained.

[0191] Step 5: Crushing Step

[0192] Subsequently, a step of preparing super absorbent polymer particles is performed by pulverizing the dried super absorbent polymer particles.

[0193] Specifically, the pulverization step may be performed to have a normal particle size, that is, a particle size of 150 μm to 850 μm, by pulverizing the dried super absorbent polymer particles.

[0194] The pulverizer used for this purpose may be a vertical pulverizer, a turbine cutter, a turbine grinder, a rotary cutting mill, a rotary mill, a disc mill, a chip crusher, a crusher, a shredder, or a disc cutter, but the present disclosure is not limited thereto.

[0195] Alternatively, a pin mill, a hammer mill, a screw mill, a roller mill, a disc mill, or a jog mill may be used as a pulverizer, but the present disclosure is not limited thereto.

[0196] At the same time, in the micronization step of the preparation method of the present disclosure, super absorbent polymer particles having a smaller particle size distribution than in the conventional shredding step can be provided, and the moisture content after drying remains relatively high. Therefore, even if pulverization is performed under mild conditions with less force, a super absorbent polymer having a very high content of normal particles with a particle size of 150 μm to 850 μm can be formed, thereby greatly reducing the generation of fine particles.

[0197] The superabsorbent polymer particles prepared as described above may include more than 80% by weight, more than 85% by weight, more than 89% by weight, more than 90% by weight, more than 92% by weight, more than 93% by weight, more than 94% by weight, or more than 95% by weight of superabsorbent polymer particles (normal particles) having a particle size of 150 μm to 850 μm, based on the total weight. The particle size of these polymer particles can be measured according to EDANA (European Disposables and Nonwovens Association) WSP 220.3.

[0198] In addition, the superabsorbent polymer particles may include about 20% by weight or less, about 18% by weight or less, about 15% by weight or less, about 13% by weight or less, about 12% by weight or less, about 111% by weight or less, about 10% by weight or less, about 9% by weight or less, about 8% by weight or less, or about 5% by weight or less of fine particles having a particle size of less than 150 μm, based on the total weight. This is in contrast to superabsorbent polymers prepared according to conventional preparation methods having fine particles greater than about 20% by weight to about 30% by weight.

[0199] Additive Addition Steps

[0200] Meanwhile, according to one embodiment of the present disclosure, before the drying step (step 4), a step of adding additives to the micronized and neutralized polymer may be further included.

[0201] The additive adding process is a process of improving physical properties by using additional additives within a range that does not impair the desired effect, and the type of additive is not particularly limited. For example, a polymerization initiator for removing residual monomers, a permeability improver for improving superabsorbency, fine particles for recycling generated fine particles, an anti-caking agent, a fluidity improver, an antioxidant, a neutralizer, a surfactant, etc. can be used, but the present disclosure is not limited thereto.

[0202] The additive adding step may be performed simultaneously with step 2, simultaneously with step 3, after step 2 and step 3, or in at least one of these steps. The additive adding step may be performed multiple times as needed, and may be performed more than once in each step.

[0203] When the additive addition step is performed separately from steps 2 and 3, ie, when it is performed after steps 2 and 3 and before step 4, this can be performed in such a way that the additive is added while the polymer is being comminuted.

[0204] The pulverization can be generally performed in the same manner as in the pulverization step of the above-mentioned step 5. In the pulverization step, the additive may be added once or more and mixed with the polymer.

[0205] Grading steps

[0206] After the step of pulverizing the super absorbent polymer particles (step 5), a step of classifying the pulverized super absorbent polymer particles according to particle size may be further included.

[0207] Surface cross-linking step

[0208] In addition, after the superabsorbent polymer particles are crushed (step 5) and / or classified, a step of forming a surface crosslinked layer on at least a portion of the surface of the superabsorbent polymer particles in the presence of a surface crosslinking agent may be further included. Through the above steps, the crosslinked polymer contained in the superabsorbent polymer particles can be further crosslinked by the surface crosslinking agent, thereby forming a surface crosslinked layer on at least a portion of the surface of the superabsorbent polymer particles.

[0209] As a surface crosslinking agent, any crosslinking agent conventionally used for preparing superabsorbent polymers can be used without any particular limitation. Examples of surface crosslinking agents may include at least one polyol selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propylene glycol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; at least one carbonate compound selected from the group consisting of ethylene carbonate, propylene carbonate and glycerol carbonate; epoxy compounds, such as ethylene glycol diglycidyl ether; oxazoline compounds, such as oxazolidinone; polyamine compounds; oxazoline compounds; mono-, di- or poly-oxazolidinone compounds; and cyclic urea compounds, etc.

[0210] Specifically, as the surface crosslinking agent, one or more, two or more, or three or more of the above surface crosslinking agents can be used. For example, ethylene carbonate-propylene carbonate (ECPC), propylene glycol and / or glycerol carbonate can be used.

[0211] The surface crosslinking agent may be used in an amount of 0.001 to 5 parts by weight based on 100 parts by weight of the superabsorbent polymer particles. For example, the amount may be 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.05 parts by weight or more, and 5 parts by weight or less, 4 parts by weight or less, or 3 parts by weight or less. When the content range of the surface crosslinking agent is adjusted within the above range, a superabsorbent polymer exhibiting excellent various physical properties may be prepared.

[0212] In addition, the step of forming the surface crosslinked layer can be performed by adding an inorganic material in addition to the surface crosslinking agent. That is, in the presence of the surface crosslinking agent and the inorganic material, the step of forming the surface crosslinked layer by further crosslinking the surface of the superabsorbent polymer particles can be performed.

[0213] As inorganic material, at least one inorganic material selected from the group consisting of silica, clay, alumina, silica-alumina composite, titanium dioxide, zinc oxide and aluminum sulfate can be used. The inorganic material can be used in powdered form or in liquid form, and in particular, aluminum oxide powder, silica-alumina powder, titanium dioxide powder or nano silicon dioxide solution can be used. In addition, based on 100 parts by weight of the superabsorbent polymer particles, the usage amount of the inorganic material can be from about 0.001 to about 1 part by weight.

[0214] In addition, the method of mixing the surface crosslinking agent with the superabsorbent polymer is not particularly limited. For example, a method of adding the surface crosslinking agent and the superabsorbent polymer composition in a reactor for mixing, a method of spraying the surface crosslinking agent on the superabsorbent polymer composition, or a method of mixing the superabsorbent polymer composition and the surface crosslinking agent while continuously supplying them to a continuously operated mixer can be used.

[0215] When the surface crosslinking agent and the superabsorbent polymer composition are mixed, water and methanol may be further mixed therewith. When water and methanol are added thereto, the advantage is that the surface crosslinking agent can be uniformly dispersed in the superabsorbent polymer composition. At this time, in order to induce uniform dispersion of the surface crosslinking agent, prevent agglomeration of the superabsorbent polymer composition, and optimize the surface penetration depth of the crosslinking agent, the addition amount of water and methanol may be appropriately controlled.

[0216] The surface crosslinking process may be performed at a temperature of about 80° C. to about 250° C. More specifically, the surface crosslinking process may be performed at a temperature of about 100° C. to about 220° C., or about 120° C. to about 200° C., for about 20 minutes to about 2 hours, or about 40 minutes to about 80 minutes. When the above surface crosslinking process conditions are met, the surfaces of the superabsorbent polymer particles are sufficiently crosslinked, thereby increasing the pressure absorption rate.

[0217] The heating means for the surface cross-linking reaction is not particularly limited. A heat medium can be supplied thereto or a heat source can be directly supplied thereto. At this time, the available heat medium can be a heating fluid, such as steam, hot air and hot oil, etc., but the present invention is not limited thereto. In addition, the temperature of the heat medium supplied thereto can be appropriately selected considering the means of the heat medium, the heating rate and the target temperature of the heating. Meanwhile, as a heat source directly supplied, an electric heater or a gas heater can be used, but the present disclosure is not limited thereto.

[0218] Post-processing steps

[0219] According to one embodiment of the present disclosure, after a surface cross-linked layer is formed on at least a portion of the surface of the superabsorbent polymer particles, at least one of a cooling step of cooling the superabsorbent polymer particles having the surface cross-linked layer formed thereon, a hydration step of adding water to the superabsorbent polymer particles having the surface cross-linked layer formed thereon, and a post-treatment step of adding an additive to the superabsorbent polymer particles having the surface cross-linked layer formed thereon may be further performed. At this time, the cooling step, the hydration step, and the post-treatment step may be performed sequentially or simultaneously.

[0220] Water or saline may be used in the hydration step, and thus the generation of residues etc. can be controlled. The amount of water used may be appropriately adjusted in consideration of the desired moisture content of the final product, and is preferably used in an amount of 0.1 to 10 wt %, 0.5 to 8 wt %, or 1 to 5 wt % based on the superabsorbent polymer, but is not limited thereto.

[0221] Furthermore, an aging step may be further performed after the hydration step.

[0222] When saline is used in the hydration step, the solution absorption rate is relatively low due to the conductivity of the saline, so the saline is uniformly diffused during the aging step, allowing the absorbent polymer to be uniformly absorbed. The aging step can be performed by a common method without particular limitation, for example, using a rotary stirring device at 100° C. or less, 80° C. or less, preferably 50° C. or less for 10 minutes to 1 hour.

[0223] The additives added in the post-treatment step may include a surfactant, an inorganic salt, a permeability improver, an anti-caking agent, a fluidity improver, an antioxidant, and the like, but the present disclosure is not limited thereto.

[0224] When the cooling step, the hydration step, and the post-treatment step are optionally performed, the generation of the residue is controlled to improve the moisture content of the final super absorbent polymer, and a high-quality super absorbent polymer product can be manufactured.

[0225] Superabsorbent polymer

[0226] The super absorbent polymer prepared by the above preparation method has a fast absorption rate and a low fine particle content, and can show similar or higher centrifuge retention capacity (CRC) and absorbency under pressure (AUP) as general absorption properties compared to super absorbent polymers prepared by conventional methods.

[0227] In addition, by narrowing the particle size distribution to have a uniform particle size distribution and reducing the extractable content (EC), a super absorbent polymer having excellent permeability and rewetting characteristics can be provided.

[0228] The absorption rate (vortex time) of the superabsorbent polymer according to one embodiment according to the vortex method can be 30 seconds or less, 28 seconds or less, 27 seconds or less, 26 seconds or less, 25 seconds or less, 24 seconds or less, 23 seconds or less, 22 seconds or less, 21 seconds or less, 20 seconds or less, 19 seconds or less, or 18 seconds or less. Since the shorter the vortex time, the better it can be evaluated, the theoretical lower limit is 0 seconds, but it can be 5 seconds or more, 10 seconds or more, or 12 seconds or more.

[0229] Hereinafter, the functions and effects of the present invention will be described in more detail by specific examples. However, these examples are only for illustrative purposes, and the present invention is not intended to be limited by these examples.

[0230] <Example>

[0231] Example 1

[0232] (Step 1: Preparation of polymer)

[0233] In a 5L glass container equipped with a stirrer and a thermometer, 1404g of acrylic acid, 4.5g of pentaerythritol triallyl ether as an internal crosslinking agent, and 3387g of water were stirred and mixed while the temperature was maintained at 5°C, and reacted while the temperature was maintained at 5°C. The glass container containing the mixture was replaced with nitrogen conditions by flowing 1000cc / min of nitrogen for 1 hour. Thereafter, 0.2g of a 30 wt% aqueous solution of hydrogen peroxide, 20.0g of a 1.6% aqueous solution of ascorbic acid, and 44g of a 1% aqueous solution of 2,2'-azobis-(2-amidinopropane) dihydrochloride were added as polymerization initiators, and 10g of a 0.01% aqueous solution of ferrous sulfate was added to initiate polymerization. After the temperature of the mixture reached 85°C, polymerization was carried out at 90±2°C for about 6 hours to obtain a polymer.

[0234] (Steps 2 and 3: Micronization, Neutralization and Addition of Additional Additives)

[0235] Glyceryl monolaurate (GML) was dissolved in water at 60° C. and added in the form of an aqueous solution at a ratio of 0.01 g / 1,000 g of the hydrogel polymer to 1,000 g of the polymer obtained in step 1. Then, it was extruded at a rotation speed of 2,500 rpm to a perforated plate having a plurality of 10 mm holes using a high-speed rotary chopper (F-150 / Karl Schnell) installed inside a cylindrical pulverizer to perform micronization.

[0236] Then, the recovered hydrogel polymer was extruded three times at 250 rpm using a screw extruder installed inside a cylindrical pulverizer to a perforated plate having a plurality of 10 mm holes for an additional pulverization process. 340 g of a 32% NaOH aqueous solution (step 3: neutralization step) was added to each step of the screw extruder to neutralize some of the acidic groups of the polymer. Then, 100 g of fine particles and 35.5 g of a 5% Na2SO4 aqueous solution were added in the additional additive addition step, respectively, to prepare hydrated superabsorbent polymer particles (= micronized and neutralized polymer).

[0237] (Step 4: Drying)

[0238] 1,000 g of the hydrated superabsorbent polymer particles were added to a ventilated belt dryer equipped with a perforated plate capable of changing the wind direction up and down. The polymer was uniformly dried by flowing hot air at 200° C. and 100° C. from top to bottom for 5 minutes and 10 minutes, respectively, and then flowing hot air at 100° C. from bottom to top for 15 minutes to prepare a dried superabsorbent polymer having a moisture content of about 10%.

[0239] (Step 5: Crushing and Classification)

[0240] The dried super absorbent polymer was pulverized using a pulverizer (GRAN-U-LIZER™, MPE) and then classified using an ASTM standard sieve to obtain a super absorbent polymer powder having a size of 150 μm to 850 μm.

[0241] (Surface cross-linking)

[0242] Thereafter, 6 g of an aqueous surface crosslinking solution containing 0.08 g of ethylene glycol diglycidyl ether (EJ-1030J) and 0.3 g of propylene glycol was sprayed onto 100 g of a superabsorbent polymer and stirred at room temperature to uniformly distribute the surface crosslinking solution on the superabsorbent polymer powder. Then, the superabsorbent polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor and subjected to a surface crosslinking reaction. In the surface crosslinking reactor, the superabsorbent polymer powder was subjected to a surface crosslinking reaction at about 140° C. for 40 minutes, thereby obtaining a surface crosslinked superabsorbent polymer.

[0243] After the surface cross-linking process, classification was performed using an ASTM standard sieve, thereby preparing a super absorbent polymer having a particle size of 150 μm to 850 μm.

[0244] Example 2

[0245] A super absorbent polymer was prepared in the same manner as in Example 1, except that in the drying step of step 4 of Example 1, 1,000 g of the hydrated super absorbent polymer particles were added to a rotary kiln dryer as a mobile dryer, and drying was performed for 35 minutes while maintaining the temperature inside the dryer at 210°C.

[0246] Example 3

[0247] A super absorbent polymer was prepared in the same manner as in Example 1, except that in the polymerization step of step 1 of Example 1, 3.5 g of pentaerythritol triallyl ether (PETTAE) and 1.0 g of polyether polyol triacrylate were used as internal crosslinking agents.

[0248] Example 4

[0249] A super absorbent polymer was prepared in the same manner as in Example 1, except that in the polymerization step of step 1 of Example 1, 3.5 g of pentaerythritol triallyl ether (PETTAE) and 1.0 g of ethylene glycol diglycidyl ether (EJ-1030J) were used as internal crosslinking agents.

[0250] Example 5

[0251] A superabsorbent polymer was prepared in the same manner as in Example 1, except that after the neutralization step in step 3 of Example 1, the additional additive addition step was changed by adding 10 g of a 1% sodium persulfate (Na2S2O8) aqueous solution and 10 g of a 1% sodium metabisulfite (Na2S2O5) aqueous solution.

[0252] Example 6

[0253] A super absorbent polymer was prepared in the same manner as in Example 1, except that in the micronizing step of step 2 of Example 1, the rotation speed of the high-speed rotary chopper was adjusted to 3,400 rpm.

[0254] Example 7

[0255] A super absorbent polymer was prepared in the same manner as in Example 1, except that the surfactant GML was not used in the micronization step of Step 2 of Example 1.

[0256] Comparative Example 1

[0257] (Step 1′: Polymer preparation - neutralization and foaming polymerization)

[0258] In a 5L glass container equipped with a stirrer and a thermometer, 982g of acrylic acid, 2.25g of ethylene glycol diglycidyl ether as an internal crosslinking agent, 0.25g of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide as a photopolymerization initiator, 1.8g of F-36D as a capsule-type foaming agent, 0.22g of sodium dodecyl sulfate as a foaming stabilizer and 445.5g of water were mixed to prepare a monomer composition. Subsequently, the monomer solution was continuously supplied using a metering pump, and at the same time, 1230.1g of a 31 wt% sodium hydroxide aqueous solution was continuously line mixed to prepare a monomer aqueous solution. At this time, after confirming that the temperature of the monomer aqueous solution rose to about 72°C or more due to the heat of neutralization, it was left until the temperature cooled to 40°C. When the temperature cooled to 40°C, 71.2g of a 2 wt% sodium persulfate aqueous solution was added thereto. The solution was poured into a Vat-type tray (15 cm wide × 15 cm long) installed in a square polymerizer (where the polymerizer was provided with a light irradiation device on the top and preheated to 80°C), and then light irradiation was performed to initiate polymerization. It was confirmed that gel was generated from the surface about 15 seconds after light irradiation, and about 30 seconds later, a polymerization reaction occurred while foaming. After further reaction for 3 minutes, a sheet-like hydrogel polymer was obtained.

[0259] (Step 2′: Crushing)

[0260] The hydrogel polymer prepared in step 1 was cut into a size of 5 cm in width and 5 cm in length, and pulverized using a screw chopper (meat grinder) equipped with a perforated plate having a plurality of holes. At this time, the rotation speed of the screw chopper was 160 rpm, and the hole size of the perforated plate was 16 mm.

[0261] (Step 3′: Drying)

[0262] 1,000 g of the hydrated superabsorbent polymer particles were added to a ventilated belt dryer equipped with a perforated plate capable of changing the wind direction up and down. The polymer was uniformly dried by flowing hot air at 180° C. from bottom to top for 20 minutes and then from top to bottom for 20 minutes to prepare a dried superabsorbent polymer having a moisture content of about 3%.

[0263] (Step 4′: Crushing and Classification)

[0264] The dried super absorbent polymer was pulverized using a pulverizer (GRAN-U-LIZER™, MPE) and then classified using an ASTM standard sieve to obtain a super absorbent polymer powder having a size of 150 μm to 850 μm.

[0265] (Step 5′: Surface cross-linking)

[0266] Thereafter, 6 g of an aqueous surface crosslinking solution containing 0.08 g of ethylene glycol diglycidyl ether (EJ-1030J) and 0.3 g of propylene glycol was sprayed onto 100 g of a superabsorbent polymer and stirred at room temperature to uniformly distribute the surface crosslinking solution on the superabsorbent polymer powder. Then, the superabsorbent polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor and subjected to a surface crosslinking reaction. In the surface crosslinking reactor, the superabsorbent polymer powder was subjected to a surface crosslinking reaction at about 140° C. for 40 minutes to obtain a surface crosslinked superabsorbent polymer.

[0267] After the surface cross-linking process, classification was performed using an ASTM standard sieve, thereby preparing a super absorbent polymer having a particle size of 150 μm to 850 μm.

[0268] Comparative Example 2

[0269] A super absorbent polymer was prepared in the same manner as in Example 1, except that in the micronizing step of step 2 of Example 1, the rotation speed of the high-speed rotary chopper was adjusted to 4,500 rpm.

[0270] Comparative Example 3

[0271] A super absorbent polymer was prepared in the same manner as in Example 1, except that in the micronization step of step 2 of Example 1, the rotation speed of the high-speed rotary chopper was adjusted to 500 rpm.

[0272] Comparative Example 4

[0273] (Step 1′: Polymer preparation - neutralization and foaming polymerization)

[0274] 100 g of acrylic acid, 0.6 g of polyethylene glycol diacrylate (PEGDA, Mn=523) as a crosslinking agent, 0.008 g of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide as a photoinitiator, 0.10 g of sodium persulfate (SPS) as a thermal initiator, 0.30 g of sodium bicarbonate (SBC) as a foaming agent, 0.03 g of sodium dodecyl sulfate (SDS) as a surfactant, 123.3 g of 31.5% caustic soda (NaOH) and 38.53 g of water were mixed to prepare a monomer aqueous solution. When the monomer aqueous solution was cooled and the final temperature reached 40° C., the monomer aqueous solution was poured into a tray and, while maintaining the polymerization atmosphere temperature at 80° C., ultraviolet rays were irradiated by a UV irradiation device (irradiation amount: 10 mV / cm 2 ) was subjected to UV polymerization for 1 to 3 minutes to prepare a hydrogel polymer sheet.

[0275] (Step 2′: Micronization)

[0276] Glyceryl monolaurate (GML) was dissolved in water at 60° C. and added in the form of an aqueous solution at a ratio of 0.001 g / 100 g of the hydrogel polymer to 100 g of the polymer obtained in step 1. Then, it was extruded at a rotation speed of 2,500 rpm to a perforated plate having a plurality of 10 mm holes using a high-speed rotary chopper (F-150 / Karl Schnell) installed inside a cylindrical pulverizer to perform micronization.

[0277] Then, the recovered hydrogel polymer was extruded through a perforated plate having a plurality of 10 mm holes three times at a rotation speed of 250 rpm using a screw extruder installed inside a cylindrical pulverizer to perform an additional pulverization process, thereby preparing hydrated super absorbent polymer particles.

[0278] (Step 3′: Drying)

[0279] 100 g of the hydrated superabsorbent polymer particles were added to a ventilated belt dryer equipped with a perforated plate capable of changing the wind direction up and down. The polymer was uniformly dried by flowing hot air at 200° C. and 100° C. from top to bottom for 5 minutes and 10 minutes, respectively, and then flowing hot air at 100° C. from bottom to top for 15 minutes to prepare a dried superabsorbent polymer having a moisture content of about 10%.

[0280] (Step 4′: Crushing and Classification)

[0281] The dried super absorbent polymer was pulverized using a pulverizer (GRAN-U-LIZER™, MPE) and then classified using an ASTM standard sieve to obtain a super absorbent polymer powder having a size of 150 to 850 μm.

[0282] (Step 5′: Surface cross-linking)

[0283] Thereafter, 6 g of an aqueous surface crosslinking solution containing 0.08 g of ethylene glycol diglycidyl ether (EJ-1030J) and 0.3 g of propylene glycol was sprayed onto 100 g of a superabsorbent polymer and stirred at room temperature to uniformly distribute the surface crosslinking solution on the superabsorbent polymer powder. Then, the superabsorbent polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor and subjected to a surface crosslinking reaction. In the surface crosslinking reactor, the superabsorbent polymer powder was subjected to a surface crosslinking reaction at about 140° C. for 40 minutes to obtain a surface crosslinked superabsorbent polymer.

[0284] After the surface cross-linking process, classification was performed using an ASTM standard sieve, thereby preparing a super absorbent polymer having a particle size of 150 μm to 850 μm.

[0285] Comparative Example 5

[0286] A super absorbent polymer was prepared in the same manner as in Comparative Example 4, except that in the micronizing step of step 2' of Comparative Example 4, the rotation speed of the high-speed rotary chopper was adjusted to 1,500 rpm.

[0287] <Experimental example>

[0288] The physical properties of the superabsorbent polymer obtained in one of the Examples and Comparative Examples were evaluated in the following manner and are listed in Table 1 below.

[0289] Unless otherwise stated, all procedures were performed in a constant temperature and humidity chamber (23±1°C, 50±10% relative humidity), and physiological saline or saline refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution.

[0290] In addition, the conductivity of tap water used in the rewetting evaluation was 170 to 180 μS / cm when measured using Orion Star A222 (Company: Thermo Scientific).

[0291] Unless otherwise stated, the physical properties of the final surface cross-linked superabsorbent polymer were evaluated using a polymer having a particle size of 150 μm to 850 μm classified by an ASTM standard sieve.

[0292] (1) Centrifugal retention capacity (CRC)

[0293] The superabsorbent polymers prepared in Examples and Comparative Examples were measured for centrifuge retention capacity by absorbency under no-load conditions according to EDANA (European Disposables and Nonwovens Association) WSP 241.3.

[0294] Specifically, W0 (g, about 0.2 g) of the superabsorbent polymer prepared in one of the examples and comparative examples was uniformly loaded into a non-woven bag and sealed, and then immersed in physiological saline (0.9 wt % sodium chloride aqueous solution) at room temperature. After 30 minutes, the bag was centrifuged at 250G for 3 minutes to drain the water, and the mass W2 (g) of the bag was measured. In addition, after the same operation was performed without using the polymer, the mass W1 (g) of the bag was measured.

[0295] Then, CRC (g / g) was calculated using the obtained mass value according to the following Equation 1.

[0296] [Equation 1]

[0297] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0298] (2) Absorption under pressure (AUP)

[0299] The pressure absorption at 0.3 psi of the super absorbent polymers prepared in Examples and Comparative Examples was measured according to EDANA WSP 242.3.

[0300] Specifically, a 400-mesh stainless steel screen is installed in the bottom of a plastic cylinder with an inner diameter of 25 mm. At room temperature and 50% humidity, W0 (g, 0.9 g) of superabsorbent polymer is evenly spread on the screen. Thereafter, a piston capable of evenly providing a 0.3 psi load is placed thereon. Here, the outer diameter of the piston is slightly less than 25 mm, there is no gap with the inner wall of the cylinder, and the up and down movement (jig-jog) of the cylinder is not interrupted. At this time, the weight of the measuring device is W3 (g).

[0301] Subsequently, a glass filter having a diameter of 90 mm and a thickness of 5 mm was placed in a culture dish having a diameter of 150 mm, and salt water (0.9 wt % sodium chloride) was poured into the culture dish. At this time, the salt water was poured until the surface level of the salt water was equal to the upper surface of the glass filter. A piece of filter paper having a diameter of 90 mm was placed thereon. After placing the measuring device on the filter paper, the liquid was absorbed under load for 1 hour. After 1 hour, the measuring device was lifted and the weight W4 (g) was measured.

[0302] Then, the pressure absorption rate (g / g) was calculated using the obtained mass value according to the following Equation 2.

[0303] [Equation 2]

[0304] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0305] The measurement was repeated 5 times, and the average value and standard deviation were obtained.

[0306] (3) Vortex time (absorption rate)

[0307] Vortex time was measured in seconds according to the method described in International Patent Publication No. 1987-003208.

[0308] Specifically, 2 g of the super absorbent polymer was added to 50 mL of saline at 23 to 24° C., and a magnetic bar (8 mm in diameter, 30 mm in length) was stirred at 600 rpm, and the time taken until the vortex disappeared was measured in seconds.

[0309] (4) Long-term rewetting with tap water under load (6-hour rewetting)

[0310] ① In a petri dish having a diameter of 13 cm, 4 g of super absorbent polymer was evenly spread and distributed using a spatula, and 200 g of tap water was poured in, and then, the super absorbent polymer was swollen.

[0311] ② On the superabsorbent polymer that has been swollen for 6 hours, lay 20 pieces of filter paper with a diameter of 11 cm each (manufacturer: Whatman, catalog number 1004-110, pore size 20-25 μm, diameter 11 cm), and pressurize with a 5 kg weight (0.75 psi) for 1 minute.

[0312] ③ After applying pressure for 1 minute, measure the amount of tap water that has penetrated into the filter paper (unit: g).

[0313] (5) Extractable content (EC)

[0314] The extractable content (1hEC) of 2 g of superabsorbent polymer after swelling for 1 hour is measured according to EDA NAWSP 270.3.

[0315] (6) Fine particle content

[0316] The base resin (BR) powders of the embodiments and comparative examples were classified using ASTM standard sieves with a scale of 850 μm (#20), 600 μm (#30), 300 μm (#50) and 150 μm (#100), and the weight of fine particles with a particle size of less than 150 μm was measured and expressed as a percentage based on the total weight of the base resin powder.

[0317] [Table 1]

[0318]

[0319] Referring to Table 1, it is confirmed that the super absorbent polymer of the Examples manufactured through the micronization process under specific conditions according to the preparation method of the present disclosure has a lower fine particle content and excellent absorption performance (particularly absorption rate) compared to the Comparative Examples.

[0320] Meanwhile, in the case of Comparative Example 1, it was confirmed that the centrifuge retention capacity of the base resin was greatly reduced and the generation of fine particles was significantly increased because the micronization process was not performed under high shear conditions and a large amount of chemical foaming agent was used. Therefore, the rewetting performance was also significantly reduced due to the low centrifuge retention capacity and high extractable content of the final product.

[0321] In the case of Comparative Example 2, the polymer chain structure of the polymer was damaged due to the increased shear force caused by the excessively high rpm. In this case, it was confirmed that the improvement in absorption rate was not significant, and the rewetting of the final product was significantly reduced due to the increase in extractable content caused by the damaged polymer chain structure.

[0322] In Comparative Example 3, it was confirmed that the shear force decreased due to the low rpm, and sufficient bubbles were not formed inside the polymer, so the absorption rate decreased.

[0323] In the case of Comparative Examples 4 and 5, since the neutralization process was performed in the polymerization step before micronization, the polymer itself was too hard to easily undergo the micronization process. As a result, the absorption performance was reduced compared to the Examples, and the generation of fine particles was significantly increased.

Claims

1. A method for preparing a superabsorbent polymer, The following steps are involved: Step 1: polymerizing a monomer composition containing a water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, and a polymerization initiator to form a polymer in which the water-soluble ethylenically unsaturated monomer having an acidic group and the internal crosslinking agent are crosslinked and polymerized; Step 2: micronizing the polymer at a rotation speed of 500 rpm to 4000 rpm; Step 3: neutralizing at least some of the acidic groups of the polymer; Step 4: drying the micronized and neutralized polymer to obtain dry superabsorbent polymer particles; and Step 5: preparing superabsorbent polymer particles by pulverizing the dried superabsorbent polymer particles.

2. The method for preparing a superabsorbent polymer according to claim 1, in, Step 1 is carried out in a batch reactor for more than 1 hour.

3. The method for preparing a superabsorbent polymer according to claim 1, in, Step 2 is performed at a rotation speed of 1500 rpm to 3500 rpm.

4. The method for preparing a superabsorbent polymer according to claim 1, in, Step 2 and step 3 are performed sequentially, alternately or simultaneously.

5. The method for preparing a superabsorbent polymer according to claim 1, in, Step 3 is performed by a high shear pulverizer, and the high shear pulverizer comprises: a body comprising a transport space in which the polymer is transported; a screw member rotatably mounted inside the transfer space to move the polymer; a drive motor that provides a rotational drive force to the screw member; a cutter member mounted in the body to pulverize the polymer; and A perforated plate has a plurality of holes and is capable of discharging the polymer pulverized by the cutter member to the outside of the body.

6. The method for preparing a superabsorbent polymer according to claim 5, in, The size of the holes formed in the perforated plate is 1 mm to 25 mm.

7. The method for preparing a superabsorbent polymer according to claim 1, in, Step 4 is carried out by fixed bed drying, mobile drying or a combination thereof.

8. The method for preparing a superabsorbent polymer according to claim 7, in, Step 4 is carried out at 80° C. to 200° C. by a fixed bed drying method.

9. The method for preparing a superabsorbent polymer according to claim 7, in, Step 4 is carried out at 100° C. to 300° C. by a mobile drying method.

10. The method for preparing a superabsorbent polymer according to claim 1, in, The dried superabsorbent polymer particles obtained by performing step 4 have a moisture content of 1 to 20 wt %.

11. The method for preparing a superabsorbent polymer according to claim 1, It also includes an additive adding step of mixing any one additional additive selected from the group consisting of a polymerization initiator, a neutralizer, a surfactant, fine particles, a permeability improver, an anti-caking agent and an antioxidant with the micronized and neutralized polymer before step 4.

12. The method for preparing a superabsorbent polymer according to claim 11, in, The additive adding step is performed simultaneously with step 2, simultaneously with step 3, after step 3, or in at least one of these steps.

13. The method for preparing a superabsorbent polymer according to claim 1 or claim 11, It also includes the step of forming a surface cross-linked layer on at least a portion of the surface of the superabsorbent polymer particles.